The role of plants as an environmental reservoir of chronic wasting disease prions - Ortega, Aimee Elise, author; Zabel, Mark, advisor; Mathiason, Candace, committee member; Leach, Jan, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2016)
Transmissible Spongiform Encephalopathies (TSEs) are a group of diseases caused by an abnormal version, PrPRES, of the normal cellular host protein prion protein (Prnp) termed PrPC. Disease is fatal resulting in amyloid deposits and spongiform degeneration in the brain in most but not all cases. Clinical signs can include wasting, increases in salivation, and general motor impairment but many other clinical signs exist and can vary between TSEs. PrPRES is incredibly resistant to inactivation and can withstand radiation, formalin treatment, and autoclaving to name a few tried decontamination methods whereas PrPC is degraded normally. This difference in degradation allows for differentiation between the two protein forms as PrPRES is resistant to degradation by Proteinase K. In the early 1980s this abnormal protein was discovered to be the sole causative agent of the various TSEs which at the time was a novel finding and a novel method of disease transmission. It is thought that slightly misfolded forms of PrPC occur which can then misfold further eventually forming PrPRES. PrPRES then has the ability to act as a template for conversion, converting PrPC. Numerous TSEs exist that affect both humans and a variety of animals. One of the animal TSEs is Chronic Wasting Disease (CWD) which affects cervids such as elk, deer, and moose (Cervus candensis, Odocoileus hemionus, Alces alces) and has become endemic in both free-ranging and captive herds. The exact mechanisms behind spread of CWD are unknown but research has shown that environmental reservoirs play a role in transmission dynamics. We chose to explore whether PrPRES can be detected on or inside grasses and plants naturally exposed to prions in CWD endemic areas by use of Protein Misfolding Cyclic Amplification (PMCA). Here we present novel environmental evidence showing that PrPRES can be found on the surface of multiple plants from Rocky Mountain National Park and mice inoculated with these samples are showing clinical signs of disease.